Frequency Behavior of Quartz Crystal Microbalance In Contact With Selected Solutions - Baba, Zuraidah (2007)
This thesis investigated the interfacial behavior of some selected solutions in contact with one surface of Quartz Crystal Microbalance (QCM). A device was constructed to monitor viscosity of solutions using fundamental frequency of 9 MHz and 10 MHz quartz crystal. Piezoelectric quartz crystals with gold electrodes were mounted by O-ring in between liquid flow cell. Only one side of the crystal was exposed to the solutions which were pumped through silicon tube by a peristaltic pump. The measured frequency shift was observed in order to investigate the interfacial behavior of some selected solution in contact with one surface of Quartz Crystal Microbalance (QCM). An analysis of the interaction between an AT-cut quartz crystal microbalance and various liquid system of analytical interest is presented. The analysis which included piezoelectric effects and other influences; liquid properties, experimental conditions and the characteristic of the solution are reported. Oscillation in distilled water was taken as a reference. The frequency change caused by the density (ρ, gcm¯3) and viscosity (η, gcm¯1s¯1) were found to be proportional to the square root of the product, (ρ η). The result suggested that analysis of small frequency shifts during EQCM studies needs to account for changes in ρ and η of the solution. In this work the frequency responses of the QCM in contact with the saccharide (sucrose, maltose and glucose), alliphatic alcohols groups (methanol, ethanol and 1-propanol), polyethylene glycol (degree of polymerization of 400, 4000, 10000 and 20000), urea, dimethyl sulfoxide, glycerol and aromatic hydrocarbon (hexane, benzene and toluene) were measured. Generally, all the liquid tested showed an increment of the frequency shift with increasing content of the solutes. For each solution, the frequency was recorded as the concentration increases from distilled water to a very concentrated solution. The frequency measurements carried out for saccharide solution produces the maximum changes of frequency shift compared with other solutions.